Stem cell-derived retinal pigment epithelium cell therapy: Past and future directions - Rohowetz, Landon J.; Koulen, Peter (Frontiers in Cell and Developmental Biology, 2023)
The eyes are relatively immune privileged organs, making them ideal targets for stem cell therapy. Researchers have recently developed and described straightforward protocols for differentiating embryonic and induced pluripotent stem cells into retinal pigment epithelium (RPE), making diseases affecting the RPE, such as age-related macular degeneration (AMD), viable targets for stem cell therapy. With the advent of optical coherence tomography, microperimetry, and various other diagnostic technologies, the ability to document disease progression and monitor response to treatments such as stem cell therapy has been significantly enhanced in recent years. Previous phase I/II clinical trials have employed various cell origins, transplant methods, and surgical techniques to identify safe and efficacious methods of RPE transplantation, and many more are currently underway. Indeed, findings from these studies have been promising and future carefully devised clinical trials will continue to enhance our understanding of the most effective methods of RPE-based stem cell therapy, with the hope to eventually identify treatments for disabling and currently incurable retinal diseases. The purpose of this review is to briefly outline existing outcomes from initial clinical trials, review recent developments, and discuss future directions of clinical research involving stem-cell derived RPE cell transplantation for retinal disease.